Cracking radically curable composition
By developing a composite material containing a cured composition containing a specific crosslinking agent and ethylenically unsaturated radical polymerizable molecules, the problem of difficulty in recycling the composite material at the end of its life is solved, and good recycling and mechanical properties are achieved.
Patent Information
- Application Number
- CN202380060365.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-28
AI Technical Summary
Radical curable compositions in existing composites are difficult to recycle at the end of their lifespan, while maintaining excellent integrity over their service lifespan is a challenge.
A composite material comprising a cured radically curable composition that is cleavable or soluble under a specific environment to enable the recycling of fillers. The uncured form of the composition comprises a specific crosslinker molecular component and an ethylenically unsaturated radically polymerizable molecular component with a glass transition temperature above 50°C.
The composite material has achieved good recyclability at the end of its life, while maintaining excellent mechanical and chemical resistance during its service life. The process enables the cleavage and recovery of the composition under acidic conditions without the addition of organic solvents.
Smart Images

Figure BDA0005274901660000091 
Figure BDA0005274901660000092 
Figure BDA0005274901660000101
Abstract
Description
Technical Field
[0001] The present invention relates to a composite material comprising a filler and a cleavable cured free-radically curable composition. The present invention also relates to a method for at least partially cleaving the composite material to at least partially recover the filler. Background Art
[0002] In the field of composites, the recycling and reuse of expensive reinforcing fillers (e.g. glass and carbon fibers) and / or resins has become a priority in the context of sustainability and the circular economy.
[0003] In combination with photo- or electron-beam initiation, free-radical curable resins are used to produce glass and carbon fiber composites. Although cured composites based on free-radically polymerizable groups have excellent mechanical and chemical resistance due to their dense crosslinking network, recycling remains a challenge. Decrosslinking of thermosetting resins (e.g. radiation-cured resins) or recycling of fillers in composites is significantly more difficult than composites made from thermoplastics due to the high crosslinking density of the former.
[0004] WO2015 / 164087 describes a radiation-curable composition for a pressure-sensitive adhesive (PSA) comprising a polymer prepared from a cleavable crosslinking polymer, wherein the cured composition has a low glass transition temperature (T g ). The goal is to tune the physical properties of the PSA, such as gel content, storage modulus or peel adhesion, after photochemical or thermal activation of the cleavable moiety to achieve a range of PSA application properties.
[0005] There is a need in the art for free radical curable compositions useful in composite materials that have good recyclability at end of life while maintaining excellent integrity during their useful life. SUMMARY OF THE INVENTION
[0007] It is therefore an object of the present invention to develop a composite material comprising a cured free-radically curable composition such that fibres contacted with this composition have good recyclability.
[0008] The composite material of the present invention may have one or more of the following advantages:
[0009] They can have a solidified composition that is cleavable or even soluble in certain environments and can therefore be incorporated into circular economy processes;
[0010] They can have cured compositions that are cleavable or even soluble under certain acidic conditions, even without the addition of organic solvents;
[0011] They can have cured compositions that have excellent mechanical and chemical resistance over the service life.
[0012] In a first aspect, the present invention relates to a composite material comprising a filler and a cleavable cured free radical curable composition, wherein the uncured free radical curable composition comprises the following components:
[0013] a. at least one crosslinker molecule component a having the following general formula:
[0014] E 1 -OC(R 2 )(R 3 )-XE 2 (1)
[0015] Where E 1 and E 2 Each includes an ethylenically unsaturated free radical polymerizable moiety, X is oxygen (O) or sulfur (S), R 2 and R 3 are independently selected from hydrogen, alkyl, alkenyl, alkynyl, cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heterocycloalkyl, heterocycloalkenyl, heteroaryl, alkoxyaryl, and alkoxyalkyl, or wherein C(R 2 )(R 3 ) are connected to form a cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heterocycloalkyl, heterocycloalkenyl, heteroaryl or alkoxyaryl ring structure, wherein R 2 and R 3 Independently or in C(R 2 )(R 3 ) is substituted or unsubstituted when forming a ring structure;
[0016] b. Optionally, at least one ethylenically unsaturated free-radically polymerizable molecular component b, which does not contain a portion -OC (R 2 )(R 3 )-X-;
[0017] wherein the cured material formed after polymerization of the composition has a glass transition temperature (T g ), measured by dynamic mechanical thermal analysis (DMTA), wherein the filler is an organic fiber or an inorganic fiber.
[0018] In a second aspect, the present invention relates to a method for at least partially recycling fillers and optionally pyrolyzed cured free radical curable composition in a composite material according to any embodiment of the first aspect, which comprises subjecting the cured free radical curable composition to a pyrolysis environment, the pyrolysis environment comprising at least one of the following: an aqueous liquid, an alcohol, an acid and a temperature above 40°C, preferably above 85°C. DETAILED DESCRIPTION OF THE INVENTION
[0020] As used herein and unless otherwise specified, the term "cleavable" means that the composition undergoes cleavage of covalent bonds in a cleavage environment. In this case, a specific form of cleavable is "soluble". The term "cleavage environment" refers to an environment comprising at least one of the following: an aqueous liquid, an alcohol, an acid, and a temperature above 40°C, preferably above 60°C, more preferably above 85°C. As used herein, the term "soluble" means that the composition undergoes cleavage of covalent bonds in a "cleavage environment", which is a liquid comprising at least one of the following: an aqueous liquid, an alcohol, an acid, possibly in combination with a higher temperature, whereby the composition is at least partially dissolved in the liquid. Preferably, if the cleavage environment comprises an aqueous liquid, an acid is also present. Preferably, the pH of the aqueous liquid is below 5, preferably below 4, more preferably below 3. For example, it can be 1.5-2.5 or 1.8-2.2. Preferably, the temperature does not exceed 300°C to avoid thermal degradation of the cured free radical curable composition.
[0021] In a first aspect, the present invention relates to a composite material comprising a filler and a cleavable cured free radical curable composition, wherein the uncured free radical curable composition comprises the following components:
[0022] a. at least one crosslinker molecule component of the following formula:
[0023] E 1 -OC(R 2 )(R 3 )-XE 2 (1)
[0024] Where E 1 and E 2 Each includes an ethylenically unsaturated free radical polymerizable moiety, X is oxygen (O) or sulfur (S), R 2 and R 3 are independently selected from hydrogen, alkyl, alkenyl, alkynyl, cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heterocycloalkyl, heterocycloalkenyl, heteroaryl, alkoxyaryl, and alkoxyalkyl, or wherein C(R 2 )(R 3 ) are connected to form a cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heterocycloalkyl, heterocycloalkenyl, heteroaryl or alkoxyaryl ring structure, wherein R 2 and R 3 Independently or in C(R 2 )(R 3 ) is substituted or unsubstituted when forming a ring structure;
[0025] b. Optionally, at least one ethylenically unsaturated free-radically polymerizable molecular component b which does not contain a moiety -OC(R 2 )(R 3 )-X-;
[0026] wherein the cured free radical curable composition formed after polymerization of the composition has a glass transition temperature (T g ), measured by dynamic mechanical thermal analysis, where the filler is an organic fiber or an inorganic fiber.
[0027] For clarity, unless otherwise stated, the glass transition temperature (T g ) All values quoted refer to the neat, cured free-radically curable composition in the polymerized (ie cured) state, ie without fillers, as determined by dynamic mechanical thermal analysis (abbreviated DMTA).
[0028] According to the present invention, the filler is an organic fiber or an inorganic fiber. Synthetic fibers can be organic or inorganic. Examples of synthetic inorganic fibers are glass fibers and boron fibers. Examples of organic synthetic fibers are carbon fibers, polyamide (polyaramid) fibers. Examples of organic natural fibers (or biofibers) are plant-derived fibers (from wood, sisal, hemp, coconut, cotton, kenaf, flax). Preferably, the fiber is selected from glass fibers and / or carbon fibers. The composite material of the first aspect is formed by curing a cured free radical curable composition in contact with the filler. The fiber is used as a reinforcing material in the cured free radical curable composition.
[0029] Since compounds a and b are polymerizable by free radical action, the uncured free radical curable composition of the first aspect can be cured by free radical action. For example, free radical curing can be initiated by electron beam initiation, by a combination of a photoinitiator and actinic radiation (e.g., ultraviolet radiation in the wavelength range of 200-400 nm or visible light in the wavelength range of 400-550 nm), or by thermal decomposition of a free radical initiator (e.g., a peroxide or an azo compound).
[0030] Preferably, at least one component a and optionally b produces T g The cured material has a T value above 50° C. If component b is present, it is preferably present in the composition in an amount such that after curing the overall composition forms a T g Materials with values above 50°C.
[0031] Preferably, component b has a T of more than 10°C after polymerization. g value.
[0032] The composition of the first aspect is preferably liquid at 25°C. For resin infusion composite applications, it preferably has a viscosity of less than 5000 mPa.s at 25°C. For example, its viscosity at 25°C may be less than 2500 mPa.s or less than 1000 mPa.s. A viscosity of less than 1000 mPa.s at 25°C is advantageous for preparing composites by resin infusion using the composition. Some embodiments of the present invention also provide a viscosity at 25°C in the range of 1-50 mPas.
[0033] The viscosity is measured according to DIN EN ISO 3219 using a rotational rheometer at 20 s -1 Measured at a shear rate of .
[0034] Glass transition temperature (T g ) marks the boundary between a glassy, rigid state of a polymer or polymer network and a softer, relaxed state (which may be rubbery or even fluid). A suitable method for determining the glass transition temperature of a solid polymer or polymer network is dynamic mechanical thermal analysis, such as described in standard method ASTM D4065-01 (Standard Test Method for Determining Glass Transition Temperature by Dynamic Mechanical Analysis).
[0035] Preferably, the T of the cured free radical curable composition is g It may be greater than 60° C., more preferably greater than 75° C. Typically, it is below 160° C., for example below 140° C.
[0036] After curing, the free radical curable composition should meet the mechanical property requirements for composite applications. Young's modulus or tensile modulus of elasticity is a mechanical property used to measure the stiffness of a solid material. It defines the relationship between tensile stress (force per unit area) and tensile strain (relative deformation) of a material when subjected to a small uniaxial deformation. Ultimate tensile elongation (UTE) or elongation at break describes the ability of a material to resist fracture. Tensile properties are reported at a temperature of 23°C according to one of the following standard methods for determining tensile properties: ASTM D638 (Standard Test Method for Tensile Properties of Plastics), ASTM D882 (Standard Test Method for Tensile Properties of Thin Plastic Sheets), or ISO527-1 (Plastics—Determination of Tensile Properties). These measurements are made on the neat, cured free radical curable composition (i.e., without the presence of fillers).
[0037] In some embodiments, the cured free radical curable composition may have a Young's modulus of at least 10 MPa, preferably at least 100 MPa, more preferably at least 1000 or 3000 MPa.
[0038] In some embodiments, the cured free radical curable composition may have a UTE of at least 0.2%, preferably at least 0.5%, and more preferably at least 2.0%. For example, it may have a UTE of 3-15%, which is particularly advantageous when the composition is used with fillers such as glass fibers or carbon fibers.
[0039] In addition to components a and b, the composition may also contain further components.
[0040] For example, it may comprise a component c which is at least one 2 )(R 3 )-X-ethylenically unsaturated free radical polymerizable molecule, the polymerized T g The amount of the composition should be such that the T of the entire composition after curing is g Above 50° C. When present, component c is preferably present in an amount of less than 5 wt % of the total amount of components a, b and c. Preferably, component c is absent.
[0041] In another embodiment, the composition may include a solvent (component d). Solvent d may be present in any amount, as it will be removed before or during curing of the composition.
[0042] It may also comprise a free-radical photoinitiator or a free-radical thermal initiator (component e).
[0043] In the general formula E 1 -OC(R 2 )(R 3 )-XE 2 In the cross-linking agent molecule component a, R 2 and R 3 Preferably independently selected from hydrogen, alkyl (e.g. C 1 -C 6 ) and aryl, or are linked together to form a ring structure of 5 or 6 carbons. In a preferred embodiment, R 2 and R 3 are independently selected from hydrogen and methyl, or are linked together such that C(R 2 )(R 3 ) to form a 5-carbon ring structure.
[0044] R 2 and R 3 Preferably, all are alkyl. Most preferably, R 2 and R 3 Neither is hydrogen, since upon hydrolysis after cleavage formaldehyde or other aldehydes such as acetaldehyde may be produced, which is not preferred for environmental reasons. In a preferred embodiment, X is an oxygen atom.
[0045] Due to E1 and E 2 In the presence of E, each cross-linker molecule can act as a cross-linker. 1 and E 2 E may independently be any moiety containing one or more ethylenically unsaturated free radical polymerizable functional groups. 1 and E 2 can be the same or different. When they are the same, this is advantageous because it is easier to prepare. However, this is not mandatory. In some embodiments, E 1 and E 2 Each may comprise a functional group independently selected from vinyl (eg vinyl ether), acrylamide, methacrylamide, acrylate functional group or methacrylate functional group. 1 and E 2 Each may contain an acryloyl functional group or a methacryloyl functional group. 1 and E 2 Each independently may contain or form a methacrylate or acrylate functional group.
[0046] When component a comprises crosslinker molecules wherein El and / or E2 comprise more than one ethylenically unsaturated free-radically polymerizable functional group, the amount of such crosslinker preferably constitutes at most 20 wt% of the crosslinker of component a.
[0047] In some embodiments, E 1 and E 2 Can be independently selected from the following formulae:
[0048] -(CO)C(R 1 )=CH 2 (5)
[0049] -L 1 -O(CO)C(R 1 )=CH 2 (6)
[0050] -L 1 -OC(R 2 )(R 3 )O(CO)C(R 1 )=CH 2 (7)
[0051] -L-XC(R 2 )(R 3 )-OL 1 -O(CO)C(R 1 )=CH 2 (8)
[0052] -L 1-(OC(R 2 )(R 3 )-O(CO)-L 2 (CO)OC(R 2 )(R 3 )OL 1 ) n OC(R 2 )(R 3 )
[0053] O(CO)C(R 1 )=CH 2 (9)
[0054] Among them, X, R 2 and R 3 As previously described for formula (1), but independently selected therefrom. Preferably, X, R 2 and R 3 With X, R in formula (1) 2 and R 3 same,
[0055] Where L 2 , L 1 and L are divalent linking groups which may be the same or different and are selected independently of each other, provided that L 2 can be a single bond, and
[0056] Where R 1 H or CH 3 , but preferably CH 3 to obtain a higher T g The cured composition.
[0057] Divalent linking group L 2 , L 1 The molecular weight of L is typically less than 2000 g / mol. In some embodiments, the molecular weight is less than 500, 250, 100, 75, or 50 g / mol.
[0058] In some preferred embodiments, the divalent linking group L 2 , L 1 Or L can be (for example, C 1 -C 6 ) alkylene group. In some embodiments, L 2 , L 1 or L is C 2 , C 3 or C 4 Alkylene group.
[0059] In some embodiments, L 2 Can be a single bond.
[0060] In some embodiments, the divalent linking group L 1 Oligomers may be included. For example, L 1 It can be the following formula:
[0061] -CH 2 CH(XH)CH 2 -DB-(-D CH 2 CH(XH)CH 2 -DB-) n -,or
[0062] -L 1’ -(-O-CHCH 3 -OLO-CHCH 3 -OL 1’ -) n -,or
[0063] -L 1’ -(-O-CHCH 3 -SLS-CHCH 3 -OL 1’ -) n -,
[0064] Where L and L 1’ Different from L 1 And among them L 1’ is a divalent linking moiety as defined above for L but independently selected,
[0065] Wherein B can be selected from alkylene, alkenylene, alkynylene, arylene, alkylene-arylene, arylene-alkylene, alkylene-arylene-alkylene, alkenylene-arylene, arylene-alkenylene, alkenylene-arylene-alkenylene, alkylene-arylene-alkenylene, alkenylene-arylene-alkylene, alkynylene-arylene, arylene-alkynylene, alkynylene-arylene-alkynylene, alkynylene-arylene-alkylene, alkylene-arylene-alkynylene, alkenylene-arylene-alkynylene, alkynylene-arylene-alkenylene, heteroarylene, alkylene-heteroarylene, heteroarylene-alkylene, alkylene-heteroarylene, heteroarylene-alkylene, alkenylene-heteroarylene, heteroarylene-alkenylene, alkylene- Heteroarylene-alkenylene, alkenylene-heteroarylene-alkylene, alkynylene-heteroarylene, heteroarylene-alkynylene, alkynylene-heteroarylene-alkynylene, alkynylene-heteroarylene-alkylene, alkylene-heteroarylene-alkynylene, alkenylene-heteroarylene-alkynylene, alkynylene-heteroarylene-alkenylene, cycloalkylene, alkylene-cycloalkylene, cycloalkylene-alkylene, alkylene-cycloalkylene-alkylene, alkenylene-cycloalkylene, cycloalkylene-alkenylene, alkenylene-cycloalkylene-alkenylene, alkylene-cycloalkylene-alkenylene, alkenylene-cycloalkylene-alkylene, alkynylene-cycloalkylene, cycloalkylene-alkynylene, alkynylene-cycloalkylene-alkynylene, alkynylene-cycloalkylene-alkylene, alkylene-cycloalkylene -alkynylene, alkenylene-cycloalkylene-alkynylene, alkynylene-cycloalkylene-alkenylene, heterocycloalkylene, alkylene-heterocycloalkylene, heterocycloalkylene-alkylene, alkylene-heterocycloalkylene-alkylene, alkenylene-heterocycloalkylene, heterocycloalkylene-alkenylene, alkenylene-heterocycloalkylene-alkenylene, alkylene-heterocycloalkylene-alkenylene, alkenylene-heterocycloalkylene-alkylene, alkynylene-heterocycloalkylene, heterocycloalkylene-alkynylene, alkynylene-heterocycloalkylene-alkynylene, alkynylene-heterocycloalkylene-alkylene, alkylene-heterocycloalkylene-alkynylene, alkenylene-heterocycloalkylene-alkynylene, alkynylene-heterocycloalkylene-alkenylene, cycloalkenylene, alkylene-cycloalkenylene, cycloalkenylene-alkylene, alkylene- Cycloalkenylene-alkylene, alkenylene-cycloalkenylene, cycloalkenylene-alkenylene, alkenylene-cycloalkenylene-alkenylene, alkylene-cycloalkenylene-alkenylene, alkenylene-cycloalkenylene-alkylene, alkynylene-cycloalkenylene, cycloalkenylene-alkynylene, alkynylene-cycloalkenylene-alkynylene, alkynylene-cycloalkenylene-alkylene, alkylene-cycloalkenylene-alkynylene, alkenylene-cycloalkenylene-alkynylene, alkynylene-cycloalkenylene-alkenylene, heterocycloalkenylene, alkylene-heterocycloalkenylene, heterocycloalkenylene-alkylene, alkylene-heterocycloalkenylene-alkylene, alkenylene-heterocycloalkenylene, heterocycloalkenylene-alkenylene, alkenylene-heterocycloalkenylene-alkenylene, alkylene-heterocycloalkenylene-alkenylene, alkenylene-heterocycloalkenylene-alkylene,Alkyne-heterocycloalkenylene, heterocycloalkenylene-alkynylene, alkynylene-heterocycloalkenylene-alkynylene, alkynylene-heterocycloalkenylene-alkylene, alkylene-heterocycloalkenylene-alkynylene, alkenylene-heterocycloalkenylene-alkynylene, alkynylene-heterocycloalkenylene-alkenylene.
[0066] B is preferably arylene-alkylene or cycloalkylene-alkylene. B is most preferably phenylene-methylene or cyclohexylene-methylene.
[0067] D and X are independently selected from O and S.
[0068] n is preferably 1-10.
[0069] Particularly preferred embodiments are those in which E1 and / or E2, more preferably E1 and E2, are -L 1 -O(CO)C(R 1 )=CH 2 (6).
[0070] In one embodiment, each or one or more of the at least one crosslinker molecule (component a) may have a general formula selected from the following:
[0071]
[0072] wherein X1 is selected from O and C(O)O, wherein C is directly bonded to L;
[0073] Where R 1 , R 2 , R 3 , L and L 1 As defined above.
[0074] Formula (2) corresponds to a preferred embodiment of formula (1) in which both E1 and E2 conform to formula (6).
[0075] Formula (3) corresponds to the embodiment of formula (1) in which E1 conforms to formula (5) and E2 conforms to formula (7). This embodiment is less preferred.
[0076] Formula (4) corresponds to the embodiment of formula (1) in which E1 conforms to formula (6) and E2 conforms to formula (8). This embodiment is less preferred.
[0077] In some embodiments, each or one or more of the at least one cross-linker molecule may have a general formula selected from the following:
[0078]
[0079]
[0080] Among them, L, D, B, X, R1 , R 2 and R 3 As defined above, L 1’ is a divalent linking moiety as defined above for L but independently selected, m is 1-10, and n is 1-10.
[0081] The cross-linking agent according to formula (2) can be synthesized, for example, as follows:
[0082]
[0083] For example, 2,2-bis(2-acryloyloxyethoxy)propane can be synthesized from 2-hydroxyethyl acrylate and dimethoxypropane as described in WO 2015 / 164087 Al to 3M:
[0084]
[0085] Alternatively, with a single -OC(R 2 )(R 3 )-O- cleavable crosslinking monomers can be synthesized from ketones or aldehydes:
[0086]
[0087] For example, 2,2-bis(2-acryloyloxyethoxy)propane can be prepared from 2-hydroxyethyl acrylate and acetone (R 2 =R 3 =CH 3 )synthesis:
[0088]
[0089] The synthesis can be achieved as follows: 2-hydroxyethyl acrylate and acetone are dissolved in tetrahydrofuran at a molar ratio of 1:1:0.8, and 0.1 equivalent of pyridinium p-toluenesulfonate (PPTS) and an appropriate amount of After 48 hours, the reaction mixture was neutralized with 0.1 equivalent of potassium carbonate. After filtration, the filtrate was evaporated to obtain the main product 2,2-bis(2-acryloyloxyethoxy)propane.
[0090] Similarly, similar reaction conditions as above can be used to prepare a 2-hydroxyethyl acrylate and acetaldehyde (R 2 =H,R 3 =CH 3 )Synthesis of 1,1-bis(2-acryloyloxyethoxy)ethane:
[0091]
[0092] Similarly, similar reaction conditions as above can be used to prepare a 2-hydroxyethyl acrylate and cyclopentanone (R 2 and R 3 =cyclopentane) to synthesize 1,1-bis(2-acryloyloxyethoxy)cyclopentane:
[0093]
[0094] Examples of ketones are: acetone, methyl ethyl ketone, acetophenone, 2-pentanone, 3-methylbutanone (methyl isopropyl ketone), 3-hexanone (ethyl propyl ketone).
[0095] Examples of cyclic ketones are: cyclopentanone, cyclohexanone and substituted analogs thereof.
[0096] Examples of aldehydes are: formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde.
[0097] The cross-linking agent according to formula (3) can be synthesized, for example, as follows:
[0098]
[0099] For example, butane-1,4-diylbis(oxy)bis(ethane-1,1-diyl) diacrylate can be synthesized by reaction of 1,4-divinyl ether with acrylic acid, as described in WO 2015 / 164087 A1 to 3M (R 1 =H, R 3 =H,L 1 =(CH 2 ) 4 ).
[0100] Or as follows:
[0101]
[0102] See Examples 11 and 12 for examples of crosslinkers prepared in this manner.
[0103] Or as follows:
[0104]
[0105] The reaction of the divinyl ether derivative with the diol may be carried out in the presence of trifluoroacetic acid or sulfonic acid.
[0106] Or as follows:
[0107]
[0108] The reaction conditions are similar to those described in the paper by Lou, Fengwen et al. on the addition of thiols to vinyl ethers to synthesize alkoxy thioethers in Acta Chimica Sinica (2010), 68(12), 1223-1228).
[0109] The cross-linking agent according to formula (4) can be synthesized, for example, as follows:
[0110]
[0111] For example, 2-(2-vinyloxyethoxy)ethyl acrylate (R 1 =H,L 1 =CH 2 CH 2 OCH 2 CH 2 ) and adipic acid (L=(CH 2 ) 4 , X=COO) was reacted in a molar ratio of 2 / 1 using THF as a solvent at 80° C. for 10 hours, and then the solvent was evaporated.
[0112] HOOCL 2 Examples of the polycarboxylic acid of COOH are phthalic acid, isophthalic acid, terephthalic acid, oxalic acid, adipic acid, succinic acid, maleic acid, malonic acid, etc., and polyesters having a residual carboxyl group.
[0113] Examples of the polyol of the formula HOLOH are ethylene glycol, diethylene glycol, tripropylene glycol, 1,6-hexanediol, neopentyl glycol, cyclohexanedimethanol and the like, polyethylene glycol, polypropylene glycol and polyesters having residual hydroxyl groups.
[0114] Examples of polythiols of the formula HSLSH are poly(ethylene glycol) dithiols, including M n It is 500-10000 g / mol of poly(ethylene glycol) dithiol.
[0115] In some embodiments, at least one crosslinker molecule component a, if polymerized together, has a g It may be greater than 60° C., preferably greater than 70° C., more preferably greater than 80° C. In some embodiments, it is above 90° C., above 100° C., or even 110° C. or higher.
[0116] In some embodiments, the amount of component a is preferably greater than 5 wt %, more preferably greater than 10 wt %, even more preferably greater than 15 wt %, still more preferably greater than 30 wt %, and most preferably greater than 50 wt % of the total amount of component a and component b.
[0117] In some embodiments, the amount of component a is preferably less than 99 wt %, more preferably less than 95 wt % of the total amount of component a and component b.
[0118] The composition may also comprise component b, namely at least one ethylenically unsaturated free-radically polymerizable molecule not comprising the moiety -OC(R 2 )(R 3 )-X-. Preferably, component b is present in the composition in an amount such that the composition forms a T greater than 50°C after curing. g Furthermore, preferably, at least one of component a and component b has a T greater than 50°C when polymerized (ie, if all molecules forming compound a are polymerized, or if all molecules forming compound b are polymerized). g , measured by DMTA. Due to the absence of part -OC(R 2 )(R 3 )-X-, component b is usually not cleavable under the cleavage conditions under which component a is cleavable.
[0119] The component b is selected from monomers, oligomers and polymers. As used herein, oligomers contain 2-10 repeating units, while polymers contain at least 11 repeating units, as determined by Mn measured by gel permeation chromatography (GPC).
[0120] In some embodiments, at least 95wt% of the component b comprises at most two free radical curable parts, preferably one free radical curable part. At most 5wt% of the component b may comprise three or more free radical curable parts. This will generally still result in significant changes in the physical properties of the cured composition when exposed to a cracking environment. In embodiments where the cured free radical curable composition is in contact with a filler, the change in this physical property may be, for example, complete dissolution, partial dissolution, or any other change that allows the cured composition to be more easily separated from the filler.
[0121] In some embodiments, each of the components b comprises at most two free radical curable moieties. This facilitates the physical properties of the cured composition to undergo significant changes when exposed to a pyrolysis environment.
[0122] In a preferred embodiment, each of the components b comprises exactly one free radical curable moiety. This is particularly advantageous in that the physical properties of the cured composition undergo significant changes when exposed to a pyrolysis environment.
[0123] Preferred free radical curable moieties are selected from acrylate and methacrylate groups.
[0124] In some embodiments, at least one of the components b comprises a hydroxyl moiety. This is advantageous because the OH moiety can promote adhesion to a substrate or filler. It is particularly advantageous to cure the composition when it is in contact with glass fibers. Examples of such components b include hydroxyalkyl (meth) acrylates, such as 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, tone TM M-100 (Dow Chemical) which is a reaction product of 2-hydroxyethyl acrylate and caprolactone, a reaction product of 2-hydroxyethyl methacrylate and caprolactone, a reaction product of 2-hydroxyethyl (meth)acrylate and ethylene oxide or propylene oxide.
[0125] Preferably, each of the components b has a T above 10°C, preferably above 20°C, preferably above 30°C, more preferably above 40°C, more preferably above 50°C after polymerization. g .
[0126] For example, 2-hydroxyethyl methacrylate polymer is characterized by having a T of 105°C for syndiotactic g value.
[0127] Preferably, component b(can consist of one or more ethylenically unsaturated free-radically polymerizable molecules, not comprising the moiety -OC(R 2 )(R 3 )-X-) is present in the composition in an amount such that the composition forms T after curing g Polymers above 50°C.
[0128] If components a and b independently lead to T g Above 50°C, any amount of component b will satisfy the requirement that the composition forms T after curing. g The amount of component b may be at least 1 wt%, preferably at least 5 wt%, but may also be at least 30 wt% or even at least 50 wt% of the total amount of component a and component b.
[0129] In any other case, the type of component b and the appropriate amount of component b can be readily determined by trial and error or using the Fox equation The T of the monomers to be polymerized g Value(T gi ) and the corresponding weight fraction w i To estimate.
[0130] In some embodiments, this amount is preferably at least 1 wt%, preferably at least 5 wt%, more preferably at least 30 wt%, or at least 50 wt% of the total amount of component a and component b.
[0131] In some embodiments, the amount of component b is preferably less than 95 wt%, more preferably less than 90 wt%, even more preferably less than 85 wt%, still more preferably less than 70 wt% of the total amount of component a and component b.
[0132] In one embodiment, the cured free radical curable composition has a double bond conversion (e.g. (meth)acrylate double bond conversion) of 20-100%, preferably 70-100%, as measured by infrared spectroscopy. For tightly crosslinked polymer networks, severe cleavage conditions may be required to render the cured composition soluble to a large extent, or to obtain a cleaved composition from which fillers can be removed. Those skilled in the art will be able to find the correct cleavage environment for this purpose.
[0133] T of the cured free radical curable composition g Above 50° C. Preferably, the T of the cured free radical curable composition is g It may be above 60° C., preferably above 70° C., more preferably above 75° C. Typically, it is below 160° C., for example below 140° C.
[0134] In some embodiments, the cured free radical curable composition may have a Young's modulus of at least 10 MPa at 20°C.
[0135] To form a composite material, compound a and optionally compound b as described in the first aspect may be contacted with a filler before curing.
[0136] The composite material of the invention can be used in the automotive industry, the aerospace industry, the construction sector, marine infrastructure, the oil and gas industry, consumer goods, protective equipment, sports, and is particularly suitable for wind blades (for wind turbines), such as wind blades made from the composite material according to the first aspect.
[0137] In a second aspect, the present invention relates to a method for at least partially recycling a filler in a composite material comprising a filler contacted with a cured free radical curable composition according to any embodiment of the first aspect and an optional pyrolyzed cured free radical curable composition, comprising the following steps: subjecting the composite material to a pyrolysis environment, the pyrolysis environment comprising at least one of the following: an aqueous liquid, an alcohol, an acid and a temperature above 40°C.
[0138] In one embodiment, the method further comprises the step of recycling at least a portion of the filler and / or the cleaved cured free radical curable composition.
[0139] In a most preferred embodiment, the composite material is subjected to a pyrolysis environment without the use of organic solvents. This makes the recycling process cheaper and safer.
[0140] Preferably, the method for at least partially recycling a composite material comprising a filler in contact with a cured free radical curable composition according to any embodiment of the first aspect comprises the step of subjecting the composite material to a pyrolysis environment consisting of an aqueous liquid, an acid and a temperature above 40°C.
[0141] Preferably, the acid is acetic acid, preferably in a concentration above 15 wt% in water.
[0142] This allows the cured free radical curable composition and filler to be recyclable because it degrades the cured free radical curable composition, thereby making it at least partially soluble, thereby separating the cured free radical curable composition from the filler. When the composite material comprises glass fibers or carbon fibers, the glass fibers or carbon fibers and the resin derivative can be recovered by pyrolysis of the cured free radical curable composition.
[0143] Preferably, if the lysis environment comprises an aqueous liquid, an acid is also present. Preferably, the pH of the aqueous liquid is below 5, preferably below 4, more preferably below 3. For example, it may be 1.5-2.5 or 1.8-2.2.
[0144] Preferably, after subjecting the cured composition to a cracking environment and a suitable solvent, the soluble content is at least 20 wt%, more preferably at least 50 wt%, even more preferably at least 90 wt% or even 100 wt%, wherein the soluble content is defined as the wt% that is no longer part of the cured composition and is removed from the cured composition. A soluble content of 100 wt% means that the composition is completely decomposed or dissolved, while a soluble content of 20 wt% means that 20 wt% of the original composition is decomposed or dissolved. In some cases, this is sufficient to separate the substrate or filler. Higher temperatures can accelerate this process.
[0145] In some embodiments, the cracking environment is the temperature that rises when not using a solvent. In such an environment, the composition will be cracked and soluble once it contacts with a suitable solvent. It is also possible that a solvent is produced by cracking, and no additional solvent is needed. Under such conditions, the soluble content is at least 20wt%, more preferably at least 50wt%, even more preferably at least 90wt% or even 100wt%, wherein the soluble content is defined as no longer a part of the cured composition and will be removed from the cured composition once it contacts with a suitable solvent. The soluble content of 100wt% means that the composition decomposes or dissolves completely, and the soluble content of 20wt% means that 20wt% of the original composition decomposes or dissolves. In some cases, this is enough to separate substrates or fillers.
[0146] In this case, a suitable solvent may be an aqueous liquid or an organic solvent. Preferably, an acid is added to the solvent.
[0147] Any features of the second aspect may be as correspondingly described in any of the preceding aspects.
[0148] The present invention will now be described in detail with reference to the following non-limiting examples, which are provided for illustrative purposes only. Example
[0149] The glass transition temperature (T) was determined by dynamic mechanical thermal analysis (DMTA). g )
[0150] One suitable method for determining the glass transition temperature of a solid polymer or cured polymer network is dynamic mechanical thermal analysis, such as that described in standard method ASTM D4065-01 (Standard Test Method for Determining Glass Transition Temperature by Dynamic Mechanical Analysis).
[0151] DMTA measurements were performed using a DMA Q800 (TA Instruments) in tensile mode. The sample dimensions between the grips were typically 11 mm × 8.0 mm × 0.04 mm. Cyclic strain deformation was applied with an amplitude of 30 μm and a frequency of 1 Hz. Viscoelasticity was measured following a temperature profile with a temperature increase from -50 to 200 °C at a heating rate of 3 °C / min. T g It is determined as the maximum value of the loss factor curve (i.e. tanδ max ) temperature.
[0152] Determination of Double Bond Conversion of (Meth) Acrylic Ester
[0153] A suitable instrumental technique for determining the conversion of ethylenic unsaturation (ie double bonds) of the cured (meth)acrylate network is ATR-FTIR (Attenuated Total Reflection-Fourier Transform Infrared) spectroscopy. The procedure is conveniently described in ASTM E168 (Standard Practice for General Techniques for Quantitative Infrared Analysis) or the equivalent ASTM E1252.
[0154] More specifically, in order to compensate for the measurement fluctuations, the 1635 cm -1 The absorption peak area at (stretching v(C=C), area A 1635 ) and 1715cm -1 The carbonyl absorption band area at (v(C=O), area A 1715 The consumption of (meth)acrylate double bonds was estimated by comparing the A of the cured composition with that of the initial liquid composition. 1635 / A 1715 The ratio estimates the double bond conversion using the following formula:
[0155] DBC(%)=100[1-(A 1635 / A 1715 ) 固化的 / (A 1635 / A 1715 ) 液体 ]
[0156] Example 1: Synthesis of crosslinking agent G1
[0157] 1 mol of 1,4-bis(ethyleneoxy)butane is reacted with 2 mol of methacrylic acid to produce a crosslinking agent G1 of formula (3), wherein L 1 is the butene part, R 1 is methyl, R 3 For hydrogen.
[0158] Example 2: Synthesis of crosslinking agent G2
[0159] 1 mol of tripropylene glycol divinyl ether is reacted with 2 mol of methacrylic acid to produce a crosslinking agent G2 of formula (3), wherein L 1 With the general formula –(-OCH 2 CH(CH 3 )-) 3 -, R 1 is methyl, R 3 For hydrogen.
[0160] Example 3: Synthesis of cross-linking agent G3
[0161] Synthesis of 1,1-bis(2-acryloyloxyethoxy)cyclopentane (R 2 and R 3 connected via a cyclopentane ring).
[0162] 2-Hydroxyethyl acrylate and cyclopentanone were dissolved in tetrahydrofuran in a molar ratio of 1:1:0.8, and 0.1 equivalent of pyridinium p-toluenesulfonate (PPTS) and an appropriate amount of After 48 hours, the reaction mixture was neutralized with 0.1 equivalent of potassium carbonate. After filtration, the filtrate was evaporated to obtain the main product 1,1-bis(2-acryloyloxyethoxy)cyclopentane.
[0163] Example 4: Preparation of free radical curable composition F1
[0164] 100 pbw of crosslinker G2 and 1 pbw of photoinitiator ( The resulting free radical curable composition was coated on a glass substrate, covered with a polypropylene film, and then exposed to UV light (LED spot) at a distance of 14 cm from the substrate. ) for 3 minutes and delivered 110 mW cm at a wavelength of 365 nm -2 After polymerization, the (meth)acrylate double bond conversion rate of the cured composition was 80%. g is 110℃.
[0165] Example 5: Preparation of free radical curable composition F2
[0166] Mix 50 pbw of crosslinker G1 with 50 pbw of 2-hydroxypropyl methacrylate. Mix 1 pbw of photoinitiator ( The resulting free radical curable composition was coated on a glass substrate, covered with a polypropylene film, and then exposed to UV light (LED spot) at a distance of 14 cm from the substrate. ) for 3 minutes and delivered 110 mW cm at a wavelength of 365 nm -2 After polymerization, the (meth)acrylate double bond conversion (DBC) of the cured composition was 80%. g is 125°C.
[0167] Comparative Example 1: Preparation of free radical curable composition C1
[0168] 50 pbw of 1,6-hexanediol diacrylate and 50 pbw of 2-hydroxyethyl methacrylate were mixed. 1 pbw of photoinitiator ( The resulting free radical curable composition was coated on a glass substrate, covered with a polypropylene film, and then exposed to UV light (LED spot) at a distance of 14 cm from the substrate. ) for 3 minutes and transmitting 110 mW cm-2 at a wavelength of 365 nm for UV curing. The (meth)acrylate double bond conversion (DBC) of the cured composition after polymerization was 82%. The T g It is 101℃.
[0169] Comparative Example 2: Preparation of free radical curable composition C2
[0170] 50 pbw of 1,6-hexanediol diacrylate was mixed with 50 pbw of 2-hydroxypropyl methacrylate. 1 pbw of photoinitiator ( The resulting free radical curable composition was coated on a glass substrate, covered with a polypropylene film, and then exposed to UV light (LED spot) at a distance of 14 cm from the substrate. ) for 3 minutes and delivered 110 mW cm at a wavelength of 365 nm -2After polymerization, the (meth)acrylate double bond conversion (DBC) of the cured composition was 80%. g is 98°C.
[0171] Example 6: Preparation of free radical curable composition F3
[0172] Mix 50 pbw of crosslinker G2 with 50 pbw of 2-hydroxyethyl methacrylate. Mix 1 pbw of photoinitiator ( The resulting free radical curable composition was coated on a glass substrate, covered with a polypropylene film, and then exposed to UV light (LED spot) at a distance of 14 cm from the substrate. ) for 3 minutes and delivered 110 mW cm at a wavelength of 365 nm -2 After polymerization, the (meth)acrylate double bond conversion (DBC) of the cured composition was 72%. g It is 122℃.
[0173] Example 7: Preparation of free radical curable composition F4
[0174] Mix 50 pbw of crosslinker G2 with 50 pbw of 2-hydroxypropyl methacrylate. Mix 1 pbw of photoinitiator ( The resulting free radical curable composition was coated on a glass substrate, covered with a polypropylene film, and then exposed to UV light (LED spot) at a distance of 14 cm from the substrate. ) for 3 minutes and delivered 110 mW cm at a wavelength of 365 nm -2 After polymerization, the (meth)acrylate double bond conversion (DBC) of the cured composition was 73%. g It is 117℃.
[0175] Example 8: Preparation of free radical curable composition F5
[0176] 50 pbw of crosslinker G2 was mixed with 25 pbw of 2-hydroxypropyl methacrylate and 25 pbw of isobornyl methacrylate. 1 pbw of photoinitiator ( The resulting free radical curable composition was coated on a glass substrate, covered with a polypropylene film, and then exposed to UV light (LED spot) at a distance of 14 cm from the substrate. ) for 3 minutes and delivered 110 mW cm at a wavelength of 365 nm -2After polymerization, the (meth)acrylate double bond conversion (DBC) of the cured composition was 72%. g is 135°C.
[0177] Example 9: Preparation of free radical curable composition F6
[0178] 100 pbw of crosslinker G1 and 1 pbw of photoinitiator ( The resulting free radical curable composition was coated on a glass substrate, covered with a polypropylene film, and then exposed to UV light (LED spot) at a distance of 14 cm from the substrate. ) for 3 minutes and delivered 110 mW cm at a wavelength of 365 nm -2 After polymerization, the (meth)acrylate double bond conversion rate of the cured composition was 80%. g is 85℃.
[0179] Example 10: Dissolution of Cured Samples in 30% or 100% Acetic Acid
[0180] The cured compositions C1-C3 and F1-F6 were immersed in 30% acetic acid or 100% acetic acid at 80°C for one week and then at room temperature for one week. The table below shows whether the cured composition was undissolved (1), partially dissolved (2) or completely dissolved (3) after two weeks. In general, partial dissolution makes it easier to separate the cured composition from the substrate than complete insolubility. As can be seen from Examples F5 and F1, the cracking environment may be different depending on the composition. Those skilled in the art will be able to find the correct conditions.
[0181] 30% (w / v) acetic acid 100% acetic acid C1 1 1 C2 1 1 C3 1 Untested F2 2 3 F3 2 3 F4 2 3 F5 1 3 F6 3 1 F1 3 1
[0182] Comparative Example 4: Preparation of free radical curable composition C4
[0183] 100 pbw of 2-hydroxypropyl methacrylate and 1 pbw of photoinitiator ( The resulting free radical curable composition was coated on a glass substrate (substrate), covered with a polypropylene film, and then exposed to UV light (LED spot) at a distance of 14 cm from the substrate. ) for 3 minutes and delivered 110 mW cm at a wavelength of 365 nm -2 After polymerization, the (meth)acrylate double bond conversion rate of the cured composition was 100%. g It is 117℃.
[0184] Example 11: Synthesis of cross-linking agent G4
[0185] Triethylene glycol divinyl ether was reacted with adipic acid (HOOC-(CH 2 ) 4 -COOH) and then reacted with methacrylic acid, L 1 = triethylene glycol, L 2 =(CH 2 ) 4 .
[0186] 7.23 g of adipic acid and 29 g of 1,4-dioxane were added to a 50 ml glass reactor and heated to 80°C with stirring. Then 20 g of triethylene glycol divinyl ether dissolved in 10 g of 1,4-dioxane was added. The reaction mixture was further heated at 80°C for 14 hours and then the solvent was evaporated. At 1.40 ppm (CH 3 ) and 5.94 ppm -O-CH(CH 3 )-O-CO- 1 The H-NMR signal clearly demonstrates the acetal bond -O-CH(CH 3 )-OC(=O)-. 10 g of the resulting product with residual vinyl ether groups was further reacted with 3 g of methacrylic acid and heated at 50° C. for 14 hours. GPC analysis confirmed that the residual vinyl ether groups reacted with methacrylic acid (the peak shifted to a higher molecular weight). The viscosity at 25° C. was 139 mPa·s.
[0187] Example 12: Synthesis of cross-linking agent G5
[0188] 1,4-Butanediol divinyl ether is reacted with oxalic acid (HOOC-COOH) and then with methacrylic acid; L 1 =(CH 2 ) 4 , L 2 For a single key.
[0189] 10 g of 1,4-butanediol divinyl ether and 5 g of THF were added to a 50 ml glass reactor and stirred at room temperature; then 3.17 g of oxalic acid dissolved in 10 g of THF was slowly added to the reactor, and the reaction mixture was stirred at room temperature for 7 hours, and then the solvent was evaporated. 3 ) and 6.03 ppm O-CH(CH 3 )-O-CO 1 The H-NMR signal clearly demonstrates the acetal bond -O-CH(CH 3 The remaining vinyl ether groups are reacted with one equivalent of (meth)acrylic acid.
[0190] Example 13: Preparation of glass fiber composite material
[0191] A series of glass fiber composites were prepared as follows.
[0192] Will be with 1pbw 50 pbw of resin mixed with HDMAP and 0.25 pbw of bisacylphosphine oxide (two photoinitiators) was injected to form three layers and weigh 390 g / m 2 of 50pbw of glass fiber.
[0193] These infused fiber sheets were then cured as follows: Both the top and back sides were irradiated, with two Ga lamps at 80 W / cm 2 The power density was irradiated at a conveyor speed of 10 m / min, and then two Ga lamps were used at 120 W / cm 2 The power density was irradiated at a conveyor speed of 5 m / min; for the back side, two Ga lamps were used at 120 W / cm 2 The irradiation was carried out at a power density of 5 m / min at a conveyor belt speed.
[0194] Composites containing the following resins were prepared: 100% G1, 100% G2, 100% HEMA (2-hydroxyethyl methacrylate), 100% HPMA (2-hydroxypropyl methacrylate), and 100% Raylok Cl100 (a styrene-free vinyl ester-based resin specially developed for the preparation of glass fiber composites that can be cured by ultraviolet (UV) light).
[0195] Example 14: Testing of Glass Fiber Composites
[0196] The composite material of Example 13 was cut into strips of 2 x 5 cm and placed in a container for testing, wherein 30% (w / v) acetic acid was added at 80° C. The results are shown in the following table.
[0197] Resin composition in composite materials 30% (w / v) acetic acid, 80°C for one week The present invention 100%G1 Complete fiber delamination The present invention 100%G2 Complete fiber delamination Comparative Example 100% HEMA No fiber delamination Comparative Example 100%HPMA No fiber delamination Comparative Example 100%Raylok C1100 No fiber delamination
[0198] It can be seen that after one week of treatment, the fibers of the composite material of the present invention are completely separated from the resin. This is not the case in the comparative example.
[0199] Example 15: Synthesis of crosslinker G4 According to the reaction conditions similar to those described in Example 1 of WO2015164087, 2-hydroxyethyl methacrylate was reacted with 2,2-dimethoxypropane to synthesize 2,2-bis(2-methacryloyloxyethoxy)propane (dimethacrylic acid ketal).
[0200] Example 16: Preparation of free radical curable composition F7
[0201] 10pbw crosslinker G4 and 1pbw photoinitiator ( BCPK) and 90 pbw 2-hydroxypropyl methacrylate were mixed. The composition was exposed to UV light (LED spot) at a distance of 14 cm from the composition protected by a polypropylene film. ) for 3 minutes and delivered 110 mW cm at a wavelength of 365 nm -2 The resulting free radical curable composition was UV cured to prepare a cured disc with a diameter of 0.5 cm and a thickness of 1 mm. After polymerization, the conversion rate of the methacrylate double bonds of the cured composition was greater than 75%.
[0202] Example 17: Testing of Glass Fiber Composites
[0203] The composite material was prepared as described in Example 13, where F7 was used. The dissolution conditions were 30 wt% acetic acid at 100°C for 3 hours. The fibers in the composite material were easily delaminated.
Claims
1. A composite material comprising a filler and a cleavable cured free radical curable composition, wherein the uncured free radical curable composition comprises the following components: At least one crosslinker molecule component a of the following general formula: E 1 -OC(R 2 )(R 3 )-XE 2 (1), where E 1 and E 2 Each includes an ethylenically unsaturated free radical polymerizable moiety, X is oxygen (O) or sulfur (S), R 2 and R 3 are independently selected from hydrogen, alkyl, alkenyl, alkynyl, cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heterocycloalkyl, heterocycloalkenyl, heteroaryl, alkoxyaryl, and alkoxyalkyl, or wherein C(R 2 )(R 3 ) are connected to form a cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heterocycloalkyl, heterocycloalkenyl, heteroaryl or alkoxyaryl ring structure, and wherein R 2 and R 3 Independently or in C(R 2 )(R 3 ) is substituted or unsubstituted when forming a ring structure; and Optionally, at least one ethylenically unsaturated free-radically polymerizable molecular component b which does not contain the moiety -OC(R 2 )(R 3 )-X-; wherein when the composition is cured, the polymer formed by the composition has a T greater than 50°C g , measured by dynamic mechanical thermal analysis (DMTA); and wherein the filler is an organic fiber or an inorganic fiber.
2. The composite material according to claim 1, wherein component b has a T higher than 10°C after polymerization. g , measured by DMTA.
3. A composite material according to any one of the preceding claims, wherein component b is present in an amount of at least 1 wt %, preferably at least 5 wt %, more preferably at least 30 wt %, based on the total amount of component a and component b.
4. A composite material according to any one of the preceding claims, wherein the concentration of component b is less than 95 wt%.
5. A composite material according to any one of the preceding claims, wherein each of the components b comprises one or two free radical curable moieties.
6. The composite material according to any one of the preceding claims, wherein at least one of the components b comprises a hydroxyl moiety.
7. The composite material according to any one of the preceding claims, wherein E1 and E2 each comprise an acrylate moiety or a methacrylate moiety.
8. A composite material according to any one of the preceding claims, wherein the one or more crosslinker molecules have a general formula selected from the group consisting of: Where X 1 Selected from O, C(O)O, wherein C is directly bonded to L, R 1 are independently selected from hydrogen and methyl, L, L 1 and L 1’ are independently selected from a divalent linking moiety, D is independently selected from O, m is 1-10, and n is 1-10.
9. The composite material according to any one of the preceding claims, wherein the amount of component a is 5 wt% or more, based on the total amount of component a and component b.
10. The composite material according to any one of the preceding claims, wherein the free radical curable composition has a viscosity at 25°C of less than 1000 mPa.s.
11. The composite material according to any one of claims 1 to 10, having a Young's modulus at 20°C of at least 10 MPa.
12. The composite material according to any one of claims 1 to 11, wherein the filler is selected from glass fibers, carbon fibers and / or natural fibers.
13. A method for at least partially recycling the filler and optionally the cleaved cured free radical curable composition in the composite material according to any one of claims 1 to 12, comprising the following steps: - subjecting the cured free radical curable composition to a pyrolysis environment comprising at least one of: an aqueous liquid, an alcohol, an acid, and a temperature above 40°C.
14. The method of claim 13, further comprising the step of recovering at least a portion of the filler and / or the cleaved cured free radical curable composition in the composite material.
Citation Information
Patent Citations
Compositions comprising cleavable crosslinker and methods
WO2015164087A1